An analysis of the forces that determine the competitive intensity in the airline industry and the implications for strategy - Nhuta, Stephen (OpenJ-Page, 2016)
http://www.ijmra.us/project%20doc/IJPSS_SEPTEMBER2012/IJMRA-PSS1711.pdf